(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2021)
This study delves into the rich and diverse tapestry of folk music traditions in two geographically distant yet culturally vibrant regions – India and South America. Folk music serves as a mirror reflecting the cultural, historical, and social nuances of a community, making a comparative analysis an intriguing exploration of shared human experiences and unique expressions. The research employs a multidisciplinary approach, combining ethnomusicology, anthropology, and cultural studies to unravel the complexities of folk music in both regions. Through fieldwork, archival research, and interviews with local musicians and communities, this study aims to highlight the intrinsic connections and distinctive features embedded within the folk music traditions of India and South America.